If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 3x + 7x + -15 Reorder the terms: y = -15 + 3x + 7x Combine like terms: 3x + 7x = 10x y = -15 + 10x Solving y = -15 + 10x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -15 + 10x
| 9(t-99)=63 | | tan(3x)(tan(x)-1)=0 | | 8(q-95)+62=6 | | 18.36+x=25.36 | | x^2-18x+385=0 | | 10(k-92)=30 | | 0.75x+4.8=13.8 | | x+y+z=1002x+4y+0.25z=100 | | 8.5x=-59.5 | | x^4+8x^2+10=0 | | 3(h-94)=6 | | 0.75+4.8=13.8 | | 4x-10=2x-10 | | 8(v-84)+3=75 | | -8x+(-24)=24 | | -3y+0.75z=x | | 2x-5x^2+45=9 | | 18*153= | | 4x=9x+37 | | 65=5(g+12) | | 9x+37=4x | | -2(t-16)=0 | | 6-4b=24 | | 3p-5=8.2 | | 7(q-3)=35 | | 9.6(x-3.75)=-38.4 | | (5x-1)-9=0 | | 3-6(2x+5)=-87 | | 3x^2-2x+16=0 | | -3x-2(5+5x)=-88 | | 8x+7+5y=135 | | -288=-4(8-8x) |